The Volume-Quality Relationship in Antibiotic Prescribing: When More Isn't Better. (10th February 2015) - Gidengil, Courtney A.; Linder, Jeffrey A.; Hunter, Gerald; Setodji, Claude; Mehrotra, Ateev
For many surgeries and high-risk medical conditions, higher volume providers provide higher quality care. The impact of volume on more common medical conditions such as acute respiratory infections (ARIs) has not been examined. Using electronic health record data for adult ambulatory ARI visits, we divided primary care physicians into ARI volume quintiles. We fitted a linear regression model of antibiotic prescribing rates across quintiles to assess for a significant difference in trend. Higher ARI volume physicians had lower quality across a number of domains, including higher antibiotic prescribing rates, higher broad-spectrum antibiotic prescribing, and lower guideline concordance. Physicians with a higher volume of cases manage ARI very differently and are more likely to prescribe antibiotics. When they prescribe an antibiotic for a diagnosis for which an antibiotic may be indicated, they are less likely to prescribe guideline-concordant antibiotics. Given that high-volume physicians account for the bulk of ARI visits, efforts targeting this group are likely to yield important population effects in improving quality.